2012
DOI: 10.1016/j.brat.2012.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of CBT interventions for co-morbid chronic pain & insomnia: A pilot study

Abstract: Introduction Chronic pain is difficult to treat and often precedes or exacerbates sleep disturbances such as insomnia. Insomnia, in turn, can amplify the pain experience. Both conditions are associated with inflammatory processes, which may be involved in the bidirectional relationship between pain and sleep. Cognitive behavioral therapy (CBT) for pain and CBT for insomnia are evidence based interventions for, respectively, chronic pain and insomnia. The study objectives were to determine the feasibility of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
141
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(153 citation statements)
references
References 39 publications
9
141
2
1
Order By: Relevance
“…Thus, improved sleep quality may improve the physiological response to stress for these patients and could be a potential mechanism of change in the treatment of CFS. Palesh et al found that sleep disruption was related to a flattened cortisol response on the TSST (43). Our result is in line with this, though we found that for patients who already displayed a flattened cortisol response on the TSST, improved insomnia severity is related to having improved cortisol response.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, improved sleep quality may improve the physiological response to stress for these patients and could be a potential mechanism of change in the treatment of CFS. Palesh et al found that sleep disruption was related to a flattened cortisol response on the TSST (43). Our result is in line with this, though we found that for patients who already displayed a flattened cortisol response on the TSST, improved insomnia severity is related to having improved cortisol response.…”
Section: Discussionsupporting
confidence: 92%
“…Lastly, treatment strategies that rehabilitation professionals can use to help individuals with FM fatigue to adjust to the pain rehabilitation process include cognitive-behavioral intervention approaches, education, pharmacological therapies, and graded or low-intensity exercise strategies (Guymer & Clauw, 2002). There is also emerging evidence showing that cognitive-behavioral strategies may help individuals with insomnia and other FM symptoms (Edinger, Wohlgemuth, Krystal, & Rice, 2005;Pigeon et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Studies that the previous AHRQ review assessed as poor quality were excluded from our review. 26 One investigator extracted relevant study, population demographic, and outcomes data. Outcomes data used in analyses were confirmed by a second investigator.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, methodological limitations have prevented conclusive evidence synthesis for these treatments. [21][22][23][24][25][26][27][28][29][30] Insomnia treatment goals include meaningful improvements in sleep and associated distress and/or dysfunction. Insomnia treatment may affect several types of outcomes.…”
Section: Introduction Backgroundmentioning
confidence: 99%